A method for separating benzene and cyclohexane using Cu-loaded ZIF-8 nanoparticles
By using Cu-loaded ZIF-8 nanoparticles as separation medium, selectively adsorb cyclohexane, the problem of high equipment cost and high energy consumption when separating benzene and cyclohexane in the prior art is solved, and an efficient and low-cost separation effect is achieved.
Patent Information
- Application Number
- CN202510012381.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-01-06
AI Technical Summary
The prior art has problems of high equipment cost and high energy consumption when separating benzene and cyclohexane, making it difficult to effectively improve separation efficiency.
Cu-loaded ZIF-8 nanoparticles are used as the separation medium, and Cu elements are loaded by impregnation method, Cu is concentrated on the surface of the nanoparticles, and cyclohexane is selectively adsorbed, thereby achieving efficient separation of benzene and cyclohexane.
The separation efficiency of benzene and cyclohexane is improved, and the separation cost and energy consumption are reduced, making this method suitable for large-scale promotion and application.
Smart Images

Figure CN119409548B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of separation and purification, and relates to a method for separating benzene and cyclohexane, and in particular to a method for separating benzene and cyclohexane by using Cu-loaded ZIF-8 nanoparticles. Background Art
[0002] The separation of benzene and cyclohexane is of great significance in the field of petrochemicals, but this process faces many challenges. 12 ) are very similar in chemical structure, which leads to very similar physical properties. The boiling point difference is only 0.6℃, which makes it difficult to effectively separate the two compounds by traditional distillation. At present, the industry usually uses complex and energy-intensive methods such as extractive distillation or azeotropic distillation to achieve separation.
[0003] CN102617262A discloses a method for separating cyclohexane-cyclohexene-benzene, which uses five distillation towers to separate cyclohexane, cyclohexene and benzene by two extraction distillations using four traditional distillation towers. Although this method reduces the energy consumption of the separation process to a certain extent, the number of distillation towers is large, the gas-liquid pipelines and operations are complex, and the equipment cost is high.
[0004] CN116854556A discloses a method for separating benzene and cyclohexane by extractive distillation coupled with a low eutectic solvent, comprising: weighing dried ammonium thiocyanate and cyclopentane sulfone according to a proportion, mixing, stirring at a given temperature to prepare a low eutectic solvent, using the low eutectic solvent formed by ammonium thiocyanate and cyclopentane sulfone as an extractant, first countercurrently extracting the benzene and cyclohexane mixture to obtain a cyclohexane product and an extract, then the extract enters an extractive distillation tower, and at the same time, the extractant enters the top of the tower for extractive distillation, the top distillate is the cyclohexane product, and the bottom distillate is the extractant and a mixture of benzene. The above method achieves the separation of benzene and cyclohexane and reduces the process energy consumption by extractive distillation coupled with extractive distillation, but there is also the problem of high equipment cost.
[0005] It can be seen that how to provide a method for separating benzene and cyclohexane to improve separation efficiency while taking into account separation cost and energy consumption has become an urgent problem that technical personnel in this field need to solve. Summary of the invention
[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for separating benzene and cyclohexane using Cu-loaded ZIF-8 nanoparticles, which improves the separation efficiency while taking into account the separation cost and energy consumption, and is conducive to large-scale promotion and application.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] The invention provides a method for separating benzene and cyclohexane by using Cu-loaded ZIF-8 nanoparticles. The method comprises: allowing a mixed solution containing benzene and cyclohexane to flow through a filler layer containing Cu-loaded ZIF-8 nanoparticles, wherein the Cu-loaded ZIF-8 nanoparticles selectively adsorb cyclohexane, thereby achieving separation of benzene and cyclohexane.
[0009] Wherein, the Cu-loaded ZIF-8 nanoparticles are loaded with Cu element by an impregnation method.
[0010] The present invention adopts Cu-loaded ZIF-8 nanoparticles as the separation medium for benzene and cyclohexane, and specifically limits the use of an impregnation method to load the Cu element on the ZIF-8 nanoparticles, so that Cu is concentrated on the surface of the nanoparticles, thereby providing more adsorption sites for cyclohexane, and finally achieving efficient separation of benzene and cyclohexane, which is conducive to large-scale promotion and application.
[0011] Preferably, the weight of the ZIF-8 nanoparticles is used as a calculation basis, and the loading amount of the Cu element in the Cu-loaded ZIF-8 nanoparticles is 2%-20%.
[0012] Preferably, the average particle size of the Cu-loaded ZIF-8 nanoparticles is 1-100 nm.
[0013] Preferably, the method for preparing the Cu-loaded ZIF-8 nanoparticles comprises the following steps:
[0014] (1) Synthesis of ZIF-8 nanoparticles;
[0015] (2) The ZIF-8 nanoparticles were loaded with Cu element by the impregnation method to obtain Cu-loaded ZIF-8 nanoparticles.
[0016] Preferably, step (1) specifically comprises: preparing a zinc ion source solution and an imidazole ligand solution respectively, pouring the imidazole ligand solution into the zinc ion source solution and stirring, and obtaining ZIF-8 nanoparticles after solid-liquid separation.
[0017] Preferably, the zinc ion source in the zinc ion source solution includes any one of zinc nitrate, zinc sulfate or zinc chloride, or a combination of at least two thereof, and more preferably zinc nitrate.
[0018] Preferably, the imidazole ligand in the imidazole ligand solution includes any one of methylimidazole, 2-methylimidazole, 4-methylimidazole or 2-ethylimidazole, or a combination of at least two thereof, and more preferably 2-methylimidazole.
[0019] Preferably, the solvents in the zinc ion source solution and the imidazole ligand solution independently include any one of methanol, ethanol or propanol or a combination of at least two of them, and methanol is more preferably used.
[0020] Preferably, the concentrations of the zinc ion source solution and the imidazole ligand solution are independently 20-60 g / L.
[0021] Preferably, the stirring temperature is 20-40°C and the stirring time is 12-36h.
[0022] Preferably, the solid-liquid separation comprises at least 2 centrifugal washes.
[0023] Preferably, the impregnation method in step (2) includes equal volume impregnation or excess volume impregnation.
[0024] Preferably, the salt solution used in the impregnation method in step (2) includes any one of copper nitrate solution, copper sulfate solution or copper chloride solution, or a combination of at least two of them.
[0025] Preferably, the impregnation method in step (2) is accompanied by stirring, and the stirring time is 0.5-1.5 h.
[0026] Preferably, the total concentration of benzene and cyclohexane in the mixed solution is 200-800 mmol / L.
[0027] Preferably, the molar ratio of benzene to cyclohexane in the mixed liquid is 1:(0.5-1).
[0028] Preferably, taking the total mass of the filler layer as a calculation basis, the filling ratio of the Cu-loaded ZIF-8 nanoparticles is 2%-10%.
[0029] Preferably, the filler in the filler layer comprises a solid phase extraction filler.
[0030] Preferably, quartz wool is respectively provided on the top and bottom of the packing layer.
[0031] Preferably, the space-time velocity of the mixed solution flowing through the packing layer is 0.2-2 (μL.min -1 ) / g.
[0032] In the present invention, the time-space velocity is specifically: the volume of the mixed liquid flowing through the packing layer per unit mass per unit time.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] The present invention adopts Cu-loaded ZIF-8 nanoparticles as the separation medium for benzene and cyclohexane, and specifically limits the use of an impregnation method to load the Cu element on the ZIF-8 nanoparticles, so that Cu is concentrated on the surface of the nanoparticles, thereby providing more adsorption sites for cyclohexane, and finally achieving efficient separation of benzene and cyclohexane, which is conducive to large-scale promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 is a TEM-EDS Mapping (transmission electron microscope-X-ray energy spectrum elemental image analysis) diagram of Cu-loaded ZIF-8 nanoparticles provided in Example 1;
[0036] Figure 2 The Pasteur tube filled with a filler layer provided in Application Example 1 and Comparative Application Example 1;
[0037] Figure 3 These are actual photos of column separation of benzene and cyclohexane in Application Example 1 and Comparative Application Example 1. DETAILED DESCRIPTION
[0038] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0039] A certain embodiment of the present invention provides a method for separating benzene and cyclohexane using Cu-loaded ZIF-8 nanoparticles, the method comprising: passing a mixed solution containing benzene and cyclohexane through a filler layer containing Cu-loaded ZIF-8 nanoparticles, the Cu-loaded ZIF-8 nanoparticles selectively adsorbing cyclohexane, thereby achieving separation of benzene and cyclohexane.
[0040] Wherein, the Cu-loaded ZIF-8 nanoparticles are loaded with Cu element by an impregnation method.
[0041] The present invention adopts Cu-loaded ZIF-8 nanoparticles as the separation medium for benzene and cyclohexane, and specifically limits the use of an impregnation method to load the Cu element on the ZIF-8 nanoparticles, so that Cu is concentrated on the surface of the nanoparticles, thereby providing more adsorption sites for cyclohexane, and finally achieving efficient separation of benzene and cyclohexane, which is conducive to large-scale promotion and application.
[0042] In certain embodiments, the mass of ZIF-8 nanoparticles is used as a calculation basis, and the loading amount of the Cu element in the Cu-loaded ZIF-8 nanoparticles is 2%-20%, for example, 2%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18% or 20%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0043] The present invention helps to maintain the structural stability and durability of ZIF-8 nanoparticles by limiting the loading amount of Cu element in Cu-loaded ZIF-8 nanoparticles. When the loading amount is less than 2%, it is difficult to achieve the expected adsorption and separation effects; when the loading amount is higher than 20%, it is easy to cause agglomeration or structural destruction of the nanoparticles, thereby affecting the separation effect.
[0044] In some embodiments, the average particle size of the Cu-loaded ZIF-8 nanoparticles is 1-100 nm, for example, 1 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm or 100 nm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0045] In certain embodiments, the method for preparing Cu-loaded ZIF-8 nanoparticles comprises the following steps:
[0046] (1) Synthesis of ZIF-8 nanoparticles;
[0047] (2) The ZIF-8 nanoparticles were loaded with Cu element by the impregnation method to obtain Cu-loaded ZIF-8 nanoparticles.
[0048] In some embodiments, step (1) specifically includes: preparing a zinc ion source solution and an imidazole ligand solution respectively, pouring the imidazole ligand solution into the zinc ion source solution and stirring, and obtaining ZIF-8 nanoparticles after solid-liquid separation.
[0049] The present invention limits the mixing mode of the zinc ion source solution and the imidazole ligand solution, and pours the imidazole ligand solution into the zinc ion source solution, thereby ensuring that the imidazole ligand is evenly distributed in the entire zinc ion source solution, thereby improving the uniformity and consistency of the obtained ZIF-8 nanoparticles. On the contrary, if the zinc ion source solution is poured into the imidazole ligand solution, it is easy to quickly form a local high concentration area near the contact surface, and because the ratio of zinc ions to imidazole ligands is too high, it is easier to grow large particles (500nm-1μm), thereby exacerbating the inhomogeneity of the ZIF-8 nanoparticles.
[0050] In certain embodiments, the zinc ion source in the zinc ion source solution includes any one of zinc nitrate, zinc sulfate or zinc chloride, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of zinc nitrate and zinc sulfate, a combination of zinc sulfate and zinc chloride, a combination of zinc nitrate and zinc chloride, or a combination of zinc nitrate, zinc sulfate and zinc chloride, and zinc nitrate is further preferred.
[0051] In certain embodiments, the imidazole ligand in the imidazole ligand solution includes any one of methylimidazole, 2-methylimidazole, 4-methylimidazole or 2-ethylimidazole, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of methylimidazole and 2-methylimidazole, a combination of 2-methylimidazole and 4-methylimidazole, or a combination of 4-methylimidazole and 2-ethylimidazole, and 2-methylimidazole is further preferred.
[0052] In certain embodiments, the solvents in the zinc ion source solution and the imidazole ligand solution independently include any one of methanol, ethanol or propanol or a combination of at least two of them. Typical but non-limiting combinations include a combination of methanol and ethanol, a combination of ethanol and propanol, a combination of methanol and propanol, or a combination of methanol, ethanol and propanol, and methanol is further preferred.
[0053] In certain embodiments, the concentrations of the zinc ion source solution and the imidazole ligand solution are independently 20-60 g / L, for example, 20 g / L, 25 g / L, 30 g / L, 35 g / L, 40 g / L, 45 g / L, 50 g / L, 55 g / L or 60 g / L, but are not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0054] In certain embodiments, the stirring temperature is 20-40°C, for example, 20°C, 22°C, 24°C, 26°C, 28°C, 30°C, 32°C, 34°C, 36°C, 38°C or 40°C, and the time is 12-36h, for example, 12h, 14h, 16h, 18h, 20h, 22h, 24h, 26h, 28h, 30h, 32h, 34h or 36h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0055] In some embodiments, the solid-liquid separation includes at least 2 centrifugal washes, for example, 2 times, 3 times, 4 times or 5 times, to fully remove the unreacted raw materials on the surface of the obtained ZIF-8 nanoparticles, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0056] In certain embodiments, the impregnation method in step (2) includes equal volume impregnation or excess volume impregnation.
[0057] In the present invention, the equal volume impregnation means that the volume of the carrier (usually refers to the pore volume) is equal to the volume of the impregnation liquid, so that the impregnation liquid can just completely enter the pores of the carrier; the excess volume impregnation means that the volume of the impregnation liquid is greater than the volume of the carrier, that is, the amount of the impregnation liquid exceeds the adsorption amount required by the carrier.
[0058] In certain embodiments, the salt solution used in the impregnation method in step (2) includes any one of copper nitrate solution, copper sulfate solution or copper chloride solution, or a combination of at least two of them. Typical but non-limiting combinations include a combination of copper nitrate solution and copper sulfate solution, a combination of copper sulfate solution and copper chloride solution, a combination of copper nitrate solution and copper chloride solution, or a combination of copper nitrate solution, copper sulfate solution and copper chloride solution.
[0059] In certain embodiments, the impregnation method in step (2) is accompanied by stirring, and the stirring time is 0.5-1.5 h, for example, 0.5 h, 0.6 h, 0.7 h, 0.8 h, 0.9 h, 1 h, 1.1 h, 1.2 h, 1.3 h, 1.4 h or 1.5 h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0060] In certain embodiments, the total concentration of benzene and cyclohexane in the mixed liquid is 200-800mmol / L, for example, it can be 200mmol / L, 250mmol / L, 300mmol / L, 350mmol / L, 400mmol / L, 450mmol / L, 500mmol / L, 550mmol / L, 600mmol / L, 650mmol / L, 700mmol / L, 750mmol / L or 800mmol / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0061] In some embodiments, the molar ratio of benzene to cyclohexane in the mixed liquid is 1:(0.5-1), for example, it can be 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9 or 1:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0062] In certain embodiments, the total mass of the filler layer is used as a calculation basis, and the filling ratio of the Cu-loaded ZIF-8 nanoparticles is 2%-10%, for example, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0063] In certain embodiments, the filler in the filler layer comprises a solid phase extraction filler.
[0064] In some embodiments, quartz wool is disposed on the top and bottom of the packing layer, respectively.
[0065] In some embodiments, the mixed solution flows through the packing layer at a space velocity of 0.2-2 (μL.min -1 ) / g, for example, it can be 0.2(μL.min -1 ) / g、0.4(μL.min -1 ) / g、0.6(μL.min -1 ) / g、0.8(μL.min -1 ) / g、1(μL.min -1 ) / g、1.2(μL.min -1 ) / g、1.4(μL.min-1 ) / g、1.6(μL.min -1 ) / g、1.8(μL.min -1 ) / g or 2(μL.min -1 ) / g, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0066] In the present invention, the time-space velocity is specifically: the volume of the mixed liquid flowing through the packing layer per unit mass per unit time. The present invention ensures that the mixed liquid has sufficient contact time with the Cu-loaded ZIF-8 nanoparticles in the packing layer by specifically limiting the time-space velocity of the mixed liquid flowing through the packing layer, thereby improving the adsorption efficiency of cyclohexane and the separation effect of benzene and cyclohexane. At the same time, under different operating environments (such as temperature and pressure), the present invention can maintain a stable separation effect and enhance the adaptability of the process by adjusting the time-space velocity of the mixed liquid flowing through the packing layer.
[0067] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0068] Example 1
[0069] This embodiment provides a Cu-loaded ZIF-8 nanoparticle and a preparation method thereof, which specifically comprises the following steps:
[0070] (1) Synthesis of ZIF-8 nanoparticles: 5.95 g Zn(NO3)2·6H2O and 6.16 g 2-methylimidazole were dissolved in 150 mL methanol to prepare zinc nitrate solution and 2-methylimidazole solution, respectively. The 2-methylimidazole solution was then slowly poured into the zinc nitrate solution and stirred at room temperature (25°C) for 24 h. The mixture was washed by centrifugation three times and then dried thoroughly to obtain ZIF-8 nanoparticles with an average particle size of 50 nm.
[0071] (2) Weigh 0.5 g of ZIF-8 nanoparticles and immerse them in a 6 g / L copper nitrate solution for over-volume impregnation. After stirring for 1 h, centrifuge and fully dry the solution to obtain Cu-loaded ZIF-8 nanoparticles.
[0072] like Figure 1 As shown, after TEM-EDS Mapping detection, the mass of ZIF-8 nanoparticles was used as the calculation basis. The loading amount of Cu element in the Cu-loaded ZIF-8 nanoparticles obtained in this example was about 10%.
[0073] Example 2
[0074] The present embodiment provides a Cu-loaded ZIF-8 nanoparticle and a preparation method thereof, except that the zinc nitrate solution is replaced by a zinc sulfate solution of equal concentration, the 2-methylimidazole solution is replaced by a 4-methylimidazole solution of equal concentration, and the copper nitrate solution is replaced by a copper sulfate solution of equal concentration, the remaining steps and conditions are the same as those in Example 1, and thus are not described in detail here.
[0075] Example 3
[0076] The present embodiment provides a Cu-loaded ZIF-8 nanoparticle and a preparation method thereof, except that the zinc nitrate solution is replaced by a zinc chloride solution of equal concentration, the 2-methylimidazole solution is replaced by a 2-ethylimidazole solution of equal concentration, and the copper nitrate solution is replaced by a copper chloride solution of equal concentration, the remaining steps and conditions are the same as those in Example 1, and thus are not described in detail here.
[0077] Example 4
[0078] The present embodiment provides a Cu-loaded ZIF-8 nanoparticle and a preparation method thereof. Except for adjusting the concentration of the copper nitrate solution so that the loading amount of the Cu element in the Cu-loaded ZIF-8 nanoparticle is about 2%, the remaining steps and conditions are the same as those in Example 1 and are not described in detail here.
[0079] Example 5
[0080] The present embodiment provides a Cu-loaded ZIF-8 nanoparticle and a preparation method thereof. Except for adjusting the concentration of the copper nitrate solution so that the loading amount of the Cu element in the Cu-loaded ZIF-8 nanoparticle is about 20%, the remaining steps and conditions are the same as those in Example 1 and are not described in detail here.
[0081] Comparative Example 1
[0082] The present comparative example provides a Cu-loaded ZIF-8 nanoparticle and a preparation method thereof, which specifically comprises: dissolving 5.95 g Zn(NO3)2·6H2O and 0.24 g Cu(NO3)2·3H2O in 150 mL methanol to obtain a metal salt solution; then dissolving 6.16 g 2-methylimidazole in 150 mL methanol to obtain a 2-methylimidazole solution; then slowly pouring the 2-methylimidazole solution into the metal salt solution, stirring at room temperature (25°C) for 24 h, centrifugally washing 3 times and then fully drying to obtain Cu-loaded ZIF-8 nanoparticles with an average particle size of 50 nm.
[0083] Comparative Example 2
[0084] The present comparative example provides a ZIF-8 nanoparticle and a preparation method thereof, which specifically comprises: dissolving 5.95 g Zn(NO3)2·6H2O and 6.16 g 2-methylimidazole in 150 mL methanol, respectively, to prepare a zinc nitrate solution and a 2-methylimidazole solution; then slowly pouring the 2-methylimidazole solution into the zinc nitrate solution, stirring at room temperature (25°C) for 24 hours, washing by centrifugation 3 times, and fully drying to obtain ZIF-8 nanoparticles with an average particle size of 50 nm.
[0085] Comparative Example 3
[0086] This comparative example provides a Cu-loaded ZIF-8 nanoparticle and a preparation method thereof. Except for adjusting the concentration of the copper nitrate solution so that the loading amount of the Cu element in the Cu-loaded ZIF-8 nanoparticle is about 1%, the remaining steps and conditions are the same as those in Example 1 and are not described in detail here.
[0087] Comparative Example 4
[0088] This comparative example provides a Cu-loaded ZIF-8 nanoparticle and a preparation method thereof. Except for adjusting the concentration of the copper nitrate solution so that the loading amount of the Cu element in the Cu-loaded ZIF-8 nanoparticle is about 25%, the remaining steps and conditions are the same as those in Example 1, and therefore are not described in detail here.
[0089] Application Example 1
[0090] This application example uses the Cu-loaded ZIF-8 nanoparticles provided in Example 1 to separate benzene and cyclohexane, specifically comprising the following steps:
[0091] (A) Weigh 2 g of solid phase extraction filler (Aladdin, quartz sand, 3-10 mesh, 2-7 mm) and 100 mg of Cu-loaded ZIF-8 nanoparticles, mix them evenly and fill them into a Pasteur tube to form a filler layer. Then fill the top and bottom of the filler layer with quartz wool (see Figure 2 Pasteur tube above);
[0092] (B) Make a liquid addition mark 5 mm above the top edge of the packing layer, and clamp the filled Pasteur tube. Add 1 mL of methanol from the top to verify the fluidity. Connect a 2 mL injection vial below so that the methanol flows through the packing layer and then into the injection vial below (see Figure 3 Pasteur tube on the left);
[0093] (C) When the liquid level in the tube drops to the liquid addition mark, add 20 μL of a mixed solution containing benzene and cyclohexane, wherein the total concentration of benzene and cyclohexane in the mixed solution is 500 mmol / L, and the molar ratio of benzene to cyclohexane is 1:0.86;
[0094] (D) Replace the lower injection vial. Thereafter, whenever the liquid level in the tube drops to the filling mark, add 500 μL of methanol to the tube and replace the lower injection vial with bottle number +1. Then, perform gas chromatography on the samples in different bottle numbers. The relevant test results are shown in Table 1 below.
[0095] Table 1
[0096]
[0097] Since the interval between sample 2 and sample 5 is 20 min, it can be inferred that the space-time velocity of the mixed liquid containing benzene and cyclohexane flowing through the packing layer is 20 μL÷(20 min×2.1 g)≈0.5 (μL.min -1 ) / g.
[0098] It can be seen from Table 1 that after the separation effect of Cu-loaded ZIF-8 nanoparticles, the molar ratio of benzene and cyclohexane in the obtained mixed solution decreased from the original 1:0.86 to 1:0.466, indicating that Cu-loaded ZIF-8 nanoparticles have a good adsorption effect on cyclohexane, and efficient separation of benzene and cyclohexane can be achieved by appropriately increasing the height of the packing layer.
[0099] Application Example 2-5
[0100] This group of application examples respectively uses the Cu-loaded ZIF-8 nanoparticles provided in Examples 2-5 to separate benzene and cyclohexane. The specific steps and conditions are the same as those in Application Example 1, so they are not repeated here.
[0101] Taking the total amount of samples in different bottle numbers as the comparison benchmark, the test results of this group of application examples are shown in Table 2 below.
[0102] Table 2
[0103]
[0104] It can be seen from Table 2 that the zinc ion source has no obvious effect on the synthesis of ZIF-8 and the separation of benzene and cyclohexane, while too much or too little Cu loading will have a certain degree of negative impact on the separation effect of benzene and cyclohexane.
[0105] Comparative application example 1
[0106] This comparative application example uses only solid phase extraction filler to separate benzene and cyclohexane, which specifically includes the following steps:
[0107] (a) Weigh 2 g of solid phase extraction filler (Aladdin, quartz sand, 3-10 mesh, 2-7 mm) and fill it into a Pasteur tube to form a filler layer, and fill the top and bottom of the filler layer with quartz wool (see Figure 2 Pasteur tube below);
[0108] (b) Make a liquid filling mark 5 mm above the top edge of the packing layer, and clamp the filled Pasteur tube. Add 1 mL of methanol from the top to verify the fluidity. Connect a 2 mL injection vial below so that the methanol flows through the packing layer and then into the injection vial below (see Figure 3 the right Pasteur tube);
[0109] (c) When the liquid level in the tube drops to the liquid addition mark, add 20 μL of a mixed solution containing benzene and cyclohexane, wherein the total concentration of benzene and cyclohexane in the mixed solution is 500 mmol / L, and the molar ratio of benzene to cyclohexane is 1:0.86;
[0110] (d) Replace the lower injection vial. Thereafter, whenever the liquid level in the tube drops to the filling mark, add 500 μL of methanol to the tube and replace the lower injection vial with bottle number +1. Perform gas chromatography on the samples in different bottle numbers. The relevant test results are shown in Table 3 below.
[0111] Table 3
[0112]
[0113] Since the interval between sample 2 and sample 4 is 5 minutes, it can be inferred that the space velocity of the mixed liquid containing benzene and cyclohexane flowing through the packing layer is 20μL÷(5min×2g)=2(μL.min -1 ) / g.
[0114] It can be seen from Table 2 that although the solid phase extraction filler itself has a certain separation effect on benzene and cyclohexane, the separation effect is obviously inferior to that of Cu-loaded ZIF-8 nanoparticles. After the industrial scale-up effect, the gap between the two will be more obvious.
[0115] Comparative Application Example 2
[0116] This comparative application example uses the Cu-loaded ZIF-8 nanoparticles provided in Comparative Example 1 to separate benzene and cyclohexane. The specific steps and conditions are the same as those in Application Example 1, so they are not repeated here.
[0117] Comparative Application Example 3
[0118] This comparative application example uses the ZIF-8 nanoparticles provided in Comparative Example 2 to separate benzene and cyclohexane. The specific steps and conditions are the same as those in Application Example 1, so they are not repeated here.
[0119] Comparative Application Example 4
[0120] This comparative application example uses the Cu-loaded ZIF-8 nanoparticles provided in Comparative Example 3 to separate benzene and cyclohexane. The specific steps and conditions are the same as those in Application Example 1, so they are not repeated here.
[0121] Comparative Application Example 5
[0122] This comparative application example uses the Cu-loaded ZIF-8 nanoparticles provided in Comparative Example 4 to separate benzene and cyclohexane. The specific steps and conditions are the same as those in Application Example 1, so they are not repeated here.
[0123] Taking the total amount of samples in different bottle numbers as the comparison benchmark, the test results of this group of comparative application examples are shown in Table 4 below.
[0124] Table 4
[0125]
[0126] It can be seen from Table 4 that the ZIF-8 material itself has a weak separation effect on benzene and cyclohexane, while the ZIF-8 material directly synthesized and doped with Cu (non-impregnation method) has a certain separation effect, but the effect is not ideal. In addition, the loading amount of Cu element will also have a significant impact on the separation effect of benzene and cyclohexane that cannot be ignored.
[0127] It can be seen that the present invention adopts Cu-loaded ZIF-8 nanoparticles as the separation medium for benzene and cyclohexane, and specifically limits the use of an impregnation method to load the Cu element on the ZIF-8 nanoparticles, so that Cu is concentrated on the surface of the nanoparticles, thereby providing more adsorption sites for cyclohexane, and ultimately achieving efficient separation of benzene and cyclohexane, which is conducive to large-scale promotion and application.
[0128] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for separating benzene and cyclohexane using Cu-loaded ZIF-8 nanoparticles, characterized in that: The method comprises: passing a mixed solution containing benzene and cyclohexane through a filler layer containing Cu-loaded ZIF-8 nanoparticles, wherein the Cu-loaded ZIF-8 nanoparticles selectively adsorb cyclohexane, thereby achieving separation of benzene and cyclohexane; The method for preparing Cu-loaded ZIF-8 nanoparticles comprises the following steps: (1) preparing a zinc ion source solution and an imidazole ligand solution respectively, pouring the imidazole ligand solution into the zinc ion source solution and stirring, and obtaining ZIF-8 nanoparticles after solid-liquid separation; (2) The ZIF-8 nanoparticles are loaded with Cu by an impregnation method to obtain Cu-loaded ZIF-8 nanoparticles, and the mass of the ZIF-8 nanoparticles is used as a calculation basis. The loading amount of the Cu element in the Cu-loaded ZIF-8 nanoparticles is 2%-20%.
2. The method according to claim 1, characterized in that The average particle size of the Cu-loaded ZIF-8 nanoparticles is 1-100 nm.
3. The method according to claim 1 or 2, characterized in that: The zinc ion source in the zinc ion source solution includes any one of zinc nitrate, zinc sulfate or zinc chloride, or a combination of at least two thereof; And / or, the imidazole ligand in the imidazole ligand solution includes any one of methylimidazole, 2-methylimidazole, 4-methylimidazole or 2-ethylimidazole, or a combination of at least two thereof; And / or, the solvents in the zinc ion source solution and the imidazole ligand solution independently include any one of methanol, ethanol or propanol or a combination of at least two thereof; And / or, the concentrations of the zinc ion source solution and the imidazole ligand solution are independently 20-60 g / L.
4. The method according to claim 1 or 2, characterized in that: The stirring temperature is 20-40°C and the stirring time is 12-36h; And / or, the solid-liquid separation comprises at least 2 centrifugal washes.
5. The method according to claim 1 or 2, characterized in that: The impregnation method in step (2) includes equal volume impregnation or over volume impregnation; And / or, the salt solution used in the impregnation method in step (2) includes any one of copper nitrate solution, copper sulfate solution or copper chloride solution, or a combination of at least two thereof; And / or, the impregnation method in step (2) is accompanied by stirring, and the stirring time is 0.5-1.5h.
6. The method according to claim 1 or 2, characterized in that: The total concentration of benzene and cyclohexane in the mixed solution is 200-800 mmol / L; And / or, the molar ratio of benzene to cyclohexane in the mixed solution is 1:(0.5-1).
7. The method according to claim 6, characterized in that Taking the total mass of the filler layer as the calculation basis, the filling ratio of the Cu-loaded ZIF-8 nanoparticles is 2%-10%; And / or, the filler in the filler layer includes a solid phase extraction filler; And / or, quartz wool is respectively arranged on the top and bottom of the packing layer.
8. The method according to claim 7, characterized in that The mixed liquid flows through the packing layer at a time-space velocity of 0.2-2 (μL.min -1 ) / g.
Citation Information
Patent Citations
Energy-saving process method for separating cyclohexane-cyclohexene-benzene
CN102617262A
Method for separating mixture of benzene, cyclohexane and cyclohexene
CN115745728A
Benzene-cyclohexene-cyclohexane separation method
CN118344236A